Biochar provides a safe and value-added solution for hyperaccumulating plant disposal: A case study of Phytolacca acinosa Roxb. (Phytolaccaceae). (July 2017) - Wang, Shengsen; Gao, Bin; Li, Yuncong; Ok, Yong Sik; Shen, Chaofeng; Xue, Shengguo
Abstract: In this work, an innovative approach using biochar technology for hyperaccumulator disposal was developed and evaluated. The heavy metal enriched P. acinosa biomass (PBM) was pyrolyzed to produce biochar (PBC). Both PBM and PBC were characterized with X-ray diffraction (XRD) for crystal phases, scanning electron microscopy (SEM) for surface topography, and analyzed for elemental composition and mobility. The results revealed that whewellite, a dominant crystal form in biomass, was decomposed to calcite after pyrolysis. Elemental analysis indicated that 91–99% total non-volatile elements in the biomass were retained in the biochar. The toxicity characteristic leaching procedure (TCLP) results revealed that 94.6% and 0.15% of total Mn was extracted for biomass and biochar, respectively. This suggests that mobility and bioavailability of Mn in biochar was much lower relative to pristine biomass. Batch sorption experiment showed that excellent removal of aqueous silver, lead, cadmium, and copper ions can be achieved with PBC. Findings from this work indicated that biochar technology can provide a value-added solution for hyperaccumulator disposal. Highlights: Biochar technology for hyperaccumulator disposal was developed and evaluated. 91–99% total non-volatile elements in the biomass were retained in the biochar. Mobility and bioavailability of Mn was greatly reduced in the biochar. Biochar showed excellent removal of aqueous silver, lead, cadmium, and copper.